Low cost methodology for estrogens monitoring in water samples using dispersive liquid - liquid microextraction and HPLC with fluorescence detection - Lima, Diana L. D. (2018)
A new low cost methodology for estrogens' analysis in water samples was developed in this work. Based on dispersive liquid-liquid microextraction followed by high-performance liquid chromatography with fluorescence detection, the developed method is fast, cheap, easy-to-use, uses low volumes of organic solvents and has the possibility of a large number of samples to be extracted in parallel. Under optimum conditions (sample volume: 8 mL; extraction solvent: 200 μL of chlorobenzene; dispersive solvent: 2000 μL of acetone), the enrichment factor and extraction recoveries were 145 and 72% for 17β-estradiol (E2) and 178 and 89% for 17α-ethinylestradiol (EE2), respectively. Limits of detection of 2.0 ng L-1for E2 and 6.5 ng L-1for EE2 were achieved, allowing the detection and quantification of these compounds in surface and waste water samples with concentrations from 12 to 32 ng L-1for E2 and from 11 to 18 ng L-1for EE2. Also, recovery tests were performed to evaluate possible matrix effects. Recoveries between 98% and 106% were obtained using humic acids (HA) to simulate the effect of organic matter, and between 86% and 120% in real water samples.